Interest when giving POAC lecture material to Accounting Students - Doni Wirshandono Yogivaria; Adi Suroso (Syntax Literate, 2023)
Changes in teaching and sophisticated times are important means to achieve more effective and efficient educational goals. But behind that, it is a big demand for lecturers to develop the ability to master learning about POAC. The role of theory and practice in the learning and teaching process is very important for educators today, because the role of learning methods about POAC can be used to channel the sender's message to the recipient and through learning methods about POAC can also help students to explain something conveyed by educators. Therefore, lecturers are required to use methods in the learning process about POAC. Thus, through the learning method about POAC can make the teaching and learning process more effective and efficient and establish good relations between lecturers and students. In addition, methods can play a role in overcoming boredom in learning in the classroom. So the learning method about POAC is one of the methods in overcoming all kinds of problems in teaching, not only overcoming problems, but the method of learning about POAC provides various comprehensive information to students.